2016
DOI: 10.1080/19320248.2016.1157545
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Indigenous Foods to Address Hidden Hunger: Nutritive Value of Indigenous Foods of Santhal Tribal Community of Jharkhand, India

Abstract: Traditional foods of indigenous communities can be explored as a sustainable means of addressing undernutrition. Our study aimed at identifying indigenous foods of the Santhal tribal community of Godda district of Jharkhand, India, assessing their nutritive value, and appraising their potential role in addressing hidden hunger. A cross-sectional survey using qualitative methods like focus group discussions with women of childbearing age (15–49 years), adult males, and elderly people was conducted for food iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…The community however, reported the historical cultivation and consumption of pearl millet, finger millet, little millet, and sorghum in the region. A similar trend on consumption of limited variety of cereals and diminishing consumption of diverse coarse cereals is observed in other tribal communities of Jharkhand as well as across India ( 23 , 40 , 57 ). Loss of coarse cereals like millets from the habitual Indian diet have been reported to have substantially reduced iron intake in the population, particularly in states where rice has replaced coarse cereals ( 58 ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The community however, reported the historical cultivation and consumption of pearl millet, finger millet, little millet, and sorghum in the region. A similar trend on consumption of limited variety of cereals and diminishing consumption of diverse coarse cereals is observed in other tribal communities of Jharkhand as well as across India ( 23 , 40 , 57 ). Loss of coarse cereals like millets from the habitual Indian diet have been reported to have substantially reduced iron intake in the population, particularly in states where rice has replaced coarse cereals ( 58 ).…”
Section: Discussionsupporting
confidence: 75%
“…NA, Not available; ND, Not detected; ¥ Laboratory analyzed; a Retinol expressed in μg/100g for animal foods . Secondary data on nutrient analysis: * ( 43 ); ∧ ( 45 ); # ( 23 ); $ ( 44 ) . β Scientific name cited from secondary sources ( 28 , 30 , 40 45 ) and € additionally verified from ( 46 , 47 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that indigenous foods and dietary diversity within an ecosystem can be powerful sources of nutrients and benefits human health (Ghosh-Jerath, Singh, Magsumbol, Kamboj, & Goldberg, 2016). Despite this fact, the use of indigenous foods has declined due to the negligence of the potential of these foods in modern commercialized and industrialized markets and lack of investment in research and development.…”
Section: Contribution Of Ethiopian Indigenous Food In Attainment Ofmentioning
confidence: 99%
“…Experimental studies on women have demonstrated the influence and significance of a wild vegetable diet in folate levels, and similar nutritional parameters [30] and specific reviews have focused on the adolescents of developed and underdeveloped countries. [31] Traditional indigenous foods have been studied to evaluate their levels of micronutrients [32], and the suitability of wild vegetables for alleviating human dietary deficiencies has been addressed [33]. Specific studies of plants that have been traditionally consumed in Spain [34] have also been made.…”
Section: Hornachos Natura 2000 Area and Wild Edible Plants: Diversitymentioning
confidence: 99%